Penerapan Metode MFEP (Multifactor Evaluation Process) Dalam Seleksi Karyawan - Nurkhalik Wahdanial Asbara; Syuryadi Syuryadi (STMIK Budi Darma, 2022)
This study aims to: (1) design a decision support system that can provide convenience for the permanent employee selection committee in making decisions about the results of the permanent employee selection. (2) implement the application of a permanent employee selection decision support system at PT. Pharos Indonesia. Designing a Decision Support System for the Selection of permanent employees at PT. Pharos Indonesia is intended to increase the effectiveness and efficiency of time in terms of decision making for the selection of permanent employees. The results of the study indicate that the system designed is very supportive of Permanent Employee Selection Decisions at PT. Pharos Indonesia by providing convenience in making objective and transparent decisions.